Proactive clinical pharmacist interventions in critical care: effect of unit speciality and other factors. (13th June 2013) - Bourne, Richard S.; Choo, Chui Lynn; Dorward, Ben J.
Abstract Background Clinical pharmacists working in critical‐care areas have a beneficial effect on a range of medication‐related therapies including improving medication safety, patient outcomes and reducing medicines' expenditure. However, there remains a lack of data on specific factors that affect the reason for and type of interventions made by clinical pharmacists, such as unit speciality. Objective To compare the type of proactive medicines‐related interventions made by clinical pharmacists on different critical‐care units within the same institution. Methods A retrospective evaluation of proactive clinical pharmacist recommendations, made in three separate critical‐care areas. Intervention data were analysed over 18 months (general units) and 2 weeks for the cardiac and neurological units. Assessment of potential patient harm related to the medication interventions were made in the neurological and cardiac units. Key findings Overall, 5623, 211 and 156 proactive recommendations were made; on average 2.2, 3.8 and 4.6 per patient from the general, neurological and cardiac units respectively. The recommendations acceptance rate by medical staff was approximately 90% for each unit. The median potential severity of patient harm averted by the interventions were 3.6 (3; 4.2) and 4 (3.2; 4.4) for the neurological and cardiac units (P = 0.059). The reasons for, types and drug classification of the medication recommendations demonstrated some significant differences between the units. Conclusions Clinical pharmacists with critical‐care training make important medication recommendations across general and specialist critical‐care units. The patient case mix and admitting speciality have some bearing on the types of medication interventions made. Moreover, severity of patient illness, scope of regular/routine specialist pharmacist service and support systems provided also probably affect the reason for these interventions.